Effect of Using River Sand on The Strength of Normal and High Strength Concrete - Al-Thairy, Haitham (International Journal of Engineering and Technology, 2018)
The shortage and high cost of quarries sand in some regions around the world has motivated engineers and researchers to investigate the possibility and feasibility of using other materials to be used as a fine aggregate in concrete mixtures. The main objective of this research is to experimentally investigate the effect of using river sand as a partial replacement of the ordinary quarries sand on the mechanical properties of normal and high strength concrete. Nine concrete mixtures were prepared and tested in terms of fresh and hardened properties using different replacement ratios of the required proportion of the normal sand. Four replacement ratios were used for normal strength concrete (NSC) which are: 0%, 25%, 50% and 75%, whereas, five replacement ratios were used for high strength concrete (HSC) namely: 0%, 35%, 60% and 90%. For each strength grade, the test parameters of the prepared mixtures included compressive and tensile strength. The experimental test results have revealed that it is possible to obtain a normal and high strength concrete with acceptable compressive and flexural strengths values by using river sand with replacement ratios up to 25% and 35% for NSC and HSC, respectively. When the replacement ratios were increased to more than the aforementioned ratios, the strength of the concrete decreased accordingly.Â Â